Glypican 4 Regulates Aβ Internalization in Neural Stem Cells Partly via Low-Density Lipoprotein Receptor-Related Protein 1 - Ma, Kaige; Xing, Shan; Luan, Yan; Zhang, Chenglin; Liu, Yingfei; Fei, Yulang; Zhang, Zhichao; Liu, Yong; Chen, Xinlin (Frontiers in Cellular Neuroscience, 2021)
Neural stem cell (NSC) damage has been reported in patients with Alzheimer’s disease. Intracellular Aβ plays a vital role in NSC damage. Heparan sulfate proteoglycans are potent mediators of Aβ enrichment in the brain. We hypothesized the heparan sulfate proteoglycan glypican 4 (Gpc4) regulates Aβ internalization by NSCs. We evaluated Gpc4 expression in NSCs from P0–P2 generations using immunofluorescence. Adenovirus and lentivirus were used to regulate Gpc4 expression in NSCs and APP/PS1 mice, respectively. Co-immunoprecipitation was used to determine the relationship between Gpc4, Aβ, and low-density lipoprotein receptor-related protein 1 (LRP1). Intracellular Aβ concentrations were detected using enzyme-linked immunosorbent assay and immunofluorescence. The role of Gpc4/LRP1 on toxic/physical Aβ-induced effects was evaluated using the JC-1 kit, terminal deoxynucleotidyl transferase dUPT nick end labeling, and western blotting. Gpc4 was stably expressed in NSCs, neurons, and astrocytes. Gpc4 was upregulated by Aβ in NSCs and regulated Aβ internalization. Gpc4 attenuation reduced Aβ uptake; Gpc4 overexpression increased Aβ uptake. Gpc4 regulated Aβ internalization through LRP1 and contributed to Aβ internalization and toxic/physical concentrations of Aβ-induced mitochondrial membrane potential and cell apoptosis, partly via LRP1. Therefore, Gpc4 is a key regulator of Aβ enrichment in NSCs. Inhibiting Gpc4 rescued the Aβ-induced toxic effect and attenuated the nontoxic Aβ enrichment into intracellular toxic concentrations. Gpc4 contributed to Aβ internalization and toxic/physical concentrations of Aβ-induced mitochondrial membrane potential damage and cell apoptosis, partly via LRP1. These findings suggest a potential role of Gpc4 in treating Alzheimer’s disease at an early stage, by targeting NSCs.